Transthoracic echocardiographic analysis of moderate to severe COVID-19 patients admitted to ICU at tertiary hospital in India - Mishra, Prashant; Mahale, Nilesh; G., Purushotham; Kale, Omkar Vivek (International Journal of Advances in Medicine, 2022)
Background: To describe the transthoracic echocardiographic findings of moderate to severe COVID-19 patients admitted to ICU. Methods: We studied the transthoracic echocardiographic findings performed within 48 hours on admission to ICU of 426 moderate to severe COVID-19 patients from July 2020 to September 2020 during their course of treatment. Echocardiographic study included left ventricular (LV) systolic and diastolic function, left ventricle wall motion abnormalities and right ventricular (RV) assessment. Results: The median age of patients was 58.2 (range 19 to 92 years) and majority of patients were male (71%). Pre-existing comorbidities were reported in 95.5% of patient’s, majority being hypertension (42.7%) and diabetes mellitus (39.2%). Abnormal echo findings were noted in 40.8% (n=174) with majority of abnormal findings noted in age group of 60-69 (n=54), men (n=114) and in patients with pre-existing coronary artery disease (CAD) (n=28). The common pattern of cardiac abnormalities was LV systolic dysfunction (n=73, 17.1%), RV dysfunction (n=30, 7%) and abnormal PA pressures (n=144, 85.2%). Abnormal echo findings were noted in 46% of patients who died and 33.9% of patients who required hospital stay of more than 10 days. Conclusions: Forty percent of admitted patients to ICU had abnormal echocardiography findings with around eighty five percent of them having raised pulmonary artery pressures. Trans-thoracic echocardiography could be used as a prognostication tool of patients admitted to COVID ICU.